HALK EĞİTİM MERKEZLERİNE DEVAM EDEN KURSİYERLERİN YAŞAM DOYUM DÜZEYLERİ VE YAŞAM BOYU ÖĞRENME EĞİLİMLERİ. - AKYOL, Bertan; BAŞARAN, Ramazan; YEŞİLBAŞ, Yasemin (Mehmet Akif Ersoy University Journal of Education Faculty, 2018)
Individuals who wish to adapt to today's changing and evolving environmental conditions are feeling the need to improve themselves by constantly learning. Lifelong learning is becoming an expectation and even a necessity for the individuals so that the societies can survive and provide a better life for the individuals. Meeting this expectation will positively affect the individual's life satisfaction and lead him to be happy. The continuance of learning all life without being restricted for a certain period of time is significant in terms of adapting to life and living as a qualified individual. In this study, it was aimed to investigate the relationship between learning and life satisfaction, which expresses well-being that is related to happiness and morale. The relationship between lifelong learning tendencies and life satisfaction perceptions of the course attendees who are attending courses at the Public Education Center in Aydın city and its districts was analyzed using the relational screening model. Lifelong learning tendencies of the 435 course attendees who participated in the research were found very high and their life satisfaction perception levels were found high. According to the results of the research, there was a significant difference between life satisfaction perceptions and gender and marital status. When perceptions of life satisfaction it was found that life satisfaction of women and married people were higher than the perceptions of life satisfaction of men and single participants. It was also found that there was a positive low-level significant relationship between life satisfaction and lifelong learning.